Performance framework for modular construction - Pham, L.; Gad, E.; Fernando, S.; Hargroves, Charlie (2017)
© 2017 Taylor & Francis Group, London. This paper presents a performance framework for modular construction. Modular construction is a method of construction that uses factory-produced building units called modules that are delivered as components, parts or whole buildings to be erected on site. The particular aspect of performance discussed in this paper is construction performance. The performance framework, in this context, is a description of the required structural characteristics of the module and its attachments for all stages of construction, from manufacturing, transport to installation. There are four elements of a performance framework: user requirement, performance description, performance parameter and evaluation. The performance framework can be used to prepare related regulation, standard, specification or check list for design and construction. The use of performance concept is encouraged because it allows innovative and efficient construction methods to be developed and still maintain a level playing field for safety and competition.